Profiteers of migration? Authoritarian states in Africa and European migration management - Anne Koch; Annette Weber; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2018)
Since 2015, the management of refugee and migration movements has been high on the agenda of the European Union (EU) and its member states. Great hopes are being pinned on development policy interventions that offer the people who are willing to migrate prospects in their home countries. This policy is accompanied by a strong focus on migration statistics. At the same time, the local contexts and regional dynamics of partner countries tend to be neglected. This is where this study comes in: What social, political, and economic processes do the EU's external migration policies encounter in African states? Which possibilities for cooperation are realistic? This study focusses on several countries that are governed in an authoritarian manner, albeit with strong variance in the degrees of authoritarianism: Egypt; the Maghreb states Algeria and Morocco; the Sahel state of Niger; as well as Sudan and Eritrea, which are linked together in a 'migration complex' at the Horn of Africa. The study analyses migration cooperation in countries with different degrees of proximity and interaction with Europe and examines whether - and to what extent - authoritarian rulers, in particular, benefit from this cooperation. The analysis shows that the impact of external EU migration policies varies according to the political, economic, and social contexts in partner countries. The respective degree of centralisation, assertiveness, creative drive, and regional ambitions of the regimes are decisive in determining whether European offers are perceived as a welcome influx of project funds or as an opportunity to pursue overarching political goals - or neither of the two. The interests in maintaining power and the legitimacy strategies of the elites play decisive roles in responding to offers of cooperation in all countries examined.
Keywords: 320